Determination of Vitamin C Concentration in Samples of Fruits and Vegetables by Volumetric Methods - Pashloa, Ezadeen; Issa, Ragiab A. M.; Said, Rehab; Mohamed, Marwa (Journal of Pure & Applied Sciences, 2022)
This research was conducted to estimate the concentration of vitamin C in fresh juices for forty-six samples of different fruits and vegetables, the concentration of vitamin C was estimated by titration method using standard iodine solution. The highest concentration of avocado sample was (268.4 mg/100ml), and the lowest value was for pear sample (11 mg/100ml). As for vegetable samples, the values ​​ranged from (222.2-11 mg/100ml), where the highest concentration was for red sweet pepper (222.2 mg /100ml). The lowest value for the two samples of cucumber and red lottery was equal (11 mg/100ml).